2020
DOI: 10.1042/bsr20200992
|View full text |Cite
|
Sign up to set email alerts
|

Potential antiviral agents of Rosmarinus officinalis extract against herpes viruses 1 and 2

Abstract: Herpes simplex viruses 1 and 2 (HSV-1 and HSV-2) belong to the herpesviridae family and cause neurological disorders by infecting the nervous system. The present study aimed to investigate the effects of Rosmarinus officinalis L. (rosemary) extract against HSV-1 and HSV-2 in vitro. The antioxidant activity of this extract was investigated by superoxide anion and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical assays. Rosemary extract was evaluated by an HSV-1 antiviral assay, in which viral replication in Ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In our experiment, rosemary extract displayed antifungal action against A. niger at concentrations ranging from 25 to 90%, which is consistent with the findings of Swari et al [ 57 ], who demonstrated that rosemary ethanol extract had an inhibitory effect against Candida albicans . Rosemary extract had antiviral efficacy against HSV-1 and HSV-2, according to Al Mergin et al [ 3 ]. Moreno et al [ 20 ] proposed that the antibacterial efficiency of rosemary extracts was linked to their unique phenolic makeup, with antimicrobial action attributed mostly to carnosic acid and rosmarinic acid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiment, rosemary extract displayed antifungal action against A. niger at concentrations ranging from 25 to 90%, which is consistent with the findings of Swari et al [ 57 ], who demonstrated that rosemary ethanol extract had an inhibitory effect against Candida albicans . Rosemary extract had antiviral efficacy against HSV-1 and HSV-2, according to Al Mergin et al [ 3 ]. Moreno et al [ 20 ] proposed that the antibacterial efficiency of rosemary extracts was linked to their unique phenolic makeup, with antimicrobial action attributed mostly to carnosic acid and rosmarinic acid.…”
Section: Resultsmentioning
confidence: 99%
“…It has been used as a stimulant, as an analgesic, and against inflammatory diseases, physical and mental fatigue in traditional medicine [ 1 ]. The pharmacologically validated medicinal properties of rosemary include antibacterial and antioxidant [ 1 , 2 ], antiviral [ 3 ], anti-inflammatory [ 4 ], antifungal [ 5 ], and antiproliferative effects toward cancer cells, absence of genotoxicity, and the ability to prolong thrombin time [ 6 ]. The antidepressant properties have been studied in various models [ 7 , 8 ]; we have earlier shown that rosemary infusion has antidepressant/anxiolytic-like and anticholinesterase effects [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that 17 (85%) of the total P. aeruginosa isolates could produce biofilm. Rosemary extract was the most useful extract in biofilm inhibition, inhabiting 83% of P. aeruginosa biofilm (25). According to the chemical analysis, the antimicrobial compounds of the Rosmarinus mainly included thymol, flavonoids, triterpenoids, and other compounds with the nature of a phenolic or free hydroxyl group, all known as the most active antimicrobial and antibiofilm compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Another important species of Lamiaceae family is Rosmarinus officinalis, which is widely used in treatment of rheumatic pain, headache, hysteria, stomachache, depression and infectious diseases (Ghasemzadeh Rahbardar et al 2020). A study reported that extract of R. officinalis, exhibited potential antiviral activity against HSV-1 and HSV-2, which this extract at the concentration of 30 μg/ml inhibited the 55% of HSV-1 and at 40μg/ml inhibited the 65% of HSV-2 plaques and extract of R. officinalis showed the significant inhibitory effect at the 50 μg/ml concentration two HSV serotypes (Al-Megrin et al 2020).…”
Section: Lamiaceaementioning
confidence: 96%